Current Research on Education 2013
DOI: 10.14257/astl.2013.36.07
|View full text |Cite
|
Sign up to set email alerts
|

School Violence in the Philippines: A Study on Programs and Policies

Abstract: Abstract.Local and international studies have affirmed the alarming situation of bullying and school violence involving Filipino children. The intensity of violence has reached a disturbing rate that has pushed policy-makers to formulate bullying prevention schemes. Despite organized attempts to make schools a safe environment, this dilemma poses critical risks that call for aggressive and determined actions to fight violence in schools. As the new academic year started in June, 2012, the Philippines' Departme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Not included in Table 2 is a discussion article by Ancho and Park (2013) on the importance of tackling school violence, including bullying and cyberbullying; and a conference report by Gonzales (2014) which summarizes views on cyberbullying from eight key professional informants.…”
Section: Philippinesmentioning
confidence: 99%
“…Not included in Table 2 is a discussion article by Ancho and Park (2013) on the importance of tackling school violence, including bullying and cyberbullying; and a conference report by Gonzales (2014) which summarizes views on cyberbullying from eight key professional informants.…”
Section: Philippinesmentioning
confidence: 99%
“…In the Philippines, different forms of abuse are experienced by one in two Filipino school children, and 50% of Filipino students are being bullied in school (Ancho & Park, 2013). In the 2019 comprehensive study of VAC in Philippine schools conducted by UNICEF, Plan International, and the Council for Welfare of Children in 2009, it was found out that there were at least 4 out of 10 children aged 6 to 10 (Grades 1-3) and 7 out of 10 aged 9 to 13 years old (Grades 4-6) and high school students aged 12 to 17 who had experienced violence in school (UNICEF, 2016b).…”
Section: Introductionmentioning
confidence: 99%
“…The Philippine education system could also incorporate classes in values education, social studies, physical education, and language education, among others with discussion on peer relation, respect and nonviolence. Lee as cited by Ancho and Park (2013) suggested that schools adopt a policy that highlights the character-building virtues such as respect, caring tolerance, and responsibility for others. The most effective (school) interventions appear to be those aimed at improving social and interpersonal skills and modifying attitudes and beliefs.…”
mentioning
confidence: 99%